Sentiments and perceptions after a privacy breach incident - Chang Boon Lee; Hio Nam Io; Heng Tang (Cogent Business & Management, 2022)
This study used sentiment analysis, keyword extraction, and content reviews to analyze related posts and comments from the Weibo microblogging website to determine the sentiments and perceptions regarding online privacy following the Facebook-Cambridge Analytica privacy breach incident. The results provide insights on users' sentiments and perceptions regarding online privacy in the Chinese context. Many comments have negative sentiments and the underlying theme of the comments is that there is no online privacy. Many users are scared of companies collecting data to support targeted advertisements because these companies know a lot about the users and the users are scared that their data could be used for inappropriate purposes. The comments also show skepticism that data collectors would protect users' data privacy. This study discusses the implications of the results for research and practice.
Keywords: 650; big data; Privacy breach; sentiment analysis